Upaya Pemberdayaan Masyarakat : Terapi Aktivitas Kelompok Berbasis Kearifan Lokal di Desa Ketapang, Kecamatan Susukan, Kabupaten Semarang - Hafidzanita First Africa; Amin, Zakki Nurul (Jurnal Bina Desa, 2025)
Mental health is still an unresolved health problem. According to the National Institute of Mental Health (NIMH) in 2030 mental disorders will account for up to 13% of all diseases and will grow to 25%. Empowerment of people with mental disorders is no less important. So as to encourage people with mental disorders to live independently, productively, and be able to restore their social functions in society. Group activity therapy is an approach to improve psychotherapy together with a number of clients simultaneously. Stages carried out (1) data collection and assessing the problems of residents with mental disorders; (2) program planning and integration of local wisdom, (3) counseling through focus group discussions, and (4) home visits. Formation of support groups consisting of nuclear family, closest family, cadres, and neighbors of residents who experience mental disorders. Through a series of group activity therapy sessions, consistent supervision of medication intake, and continuous moral support for families, this program aims not only to enhance the well-being of individuals with mental disorders but also to fortify the ties of solidarity and unity within the community.